Soluble Factors Released From Activated T Lymphocytes Regulate C2C12 Myoblast Proliferation and Cellular Signaling, but Effects Are Blunted in the Elderly. (17th October 2018) - Al-Dabbagh, Sarah; McPhee, Jamie S; Piasecki, Mathew; Stewart, Claire E; Al-Shanti, Nasser
Abstract: The key objective of this work was to investigate the impact of young and old human lymphocyte secretomes on C2C12 myoblasts regeneration. Conditioned media were harvested from isolated young and older lymphocytes treated with (activated [AC]) or without (nonactivated [NA]), anti-CD3/CD28 activators for 4 days. AC conditioned media from older lymphocytes had decreased levels of amphiregulin (367 ± 208 pg/mL vs 904 ± 323 pg/mL; p = .018) and IGF-I (845 ± 88 ng/mL vs 1100 ± 48 ng/mL; p = .032) compared with younger AC lymphocytes. AC older versus younger lymphocytes had reduced expression of CD25 (24.6 ± 5.5%; p = .0003) and increased expression of FoxP3 (35 ± 15.7%; p = .032). Treatment of C2C12 myoblasts with young AC lymphocytes resulted in decreased expression of MyoD (0.46 ± 0.12; p =.004) and Myogenin (0.34 ± 0.05; p = .010) mRNA, increased activation of MEk1 (724 ± 140 mean fluorescent intensity [MFI]; p =.001) and ERK1/2 (3768 ± 314 MFI; p =.001), and a decreased activation of Akt (74.5 ± 4 MFI; p = .009) and mTOR (61.8 ± 7 MFI; p = .001) compared with old AC lymphocytes. By contrast, C2C12 myoblasts treated with older AC lymphocytes displayed increased expression of MyoD (0.7 ± 0.08; p =.004) and Myogenin (0.68 ± 0.05; p =.010) mRNA, decreased phosphorylation of MEk1 and ERK1/2 (528 ± 80 MFI; p = .008, and 1141 ± 668 MFI; p = .001, respectively), and increased Akt/mTOR activation (171 ± 35 MFI; p = .009, and 184 ± 33 MFI; p = .001, respectively). These data provide new evidence that differences between older and younger lymphocyte secretomes contribute to differential responses of C2C12 myoblasts in culture.